PENGARUH INTEGRATED MARKETING COMMUNICATION DAN EVENT MARKETING TERHADAP KEPUTUSAN TAMU MENGINAP DI FAME HOTEL - I Made Andityawan; Gusti Ngurah Joko Adinegara; Tri Priyono Budi Santoso (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThe purpose of this study is to determine the positive effects both partially andsimultaneously between Integrated Marketing Communication (IMC) and Event Marketing onCustomer Decision to stay at Fame Hotel Sunset Road. The sample used in this study was 96people. The analytical method used is the classic assumption test, multiple linear regression test,correlation test, coefficient of determination and hypothesis testing using the help of the SPSS24.0 Software Program. Based on the results of the research, the IMC (X1) variable has a partialand significant effect on Customer Decision (Y). It is proved by the regression value of IMC (X1)which is 0.220 and sig value is below 0.05. Event Marketing (X2) has a partial and significant effecton Customer Decision (Y). It is proved by the Event Marketing (X2) regression value which is 0.457and the sig value is below 0.05. IMC (X1) and Event Marketing (X2) have a simultaneous andsignificant effect on Customer Decision (Y). This is evidenced by the value of Multiple RegressionAnalysis of Y = 6,642 + 0,220X1 + 0,457X2 + e. From the research, it can be concluded thatthere is a positive influence between IMC and Event Marketing on Customer Decision to stay bothpartially and simultaneously. Thus, the management is expected to continue to maintain andimprove in order to increase the number of guest in Fame Hotel Sunset Road Bali.Keywords: Customer Decision, Event Marketing, Hotel, Integrated Marketing Communication